2016
DOI: 10.1158/1078-0432.ccr-15-2119
|View full text |Cite
|
Sign up to set email alerts
|

Cotargeting Androgen Receptor Splice Variants and mTOR Signaling Pathway for the Treatment of Castration-Resistant Prostate Cancer

Abstract: Purpose The PI3K/Akt/mTOR pathway is activated in most castration-resistant prostate cancer (CRPC). Transcriptionally active androgen receptor (AR) plays a role in the majority of CRPC. Therefore, co-targeting full-length (FL) AR and PI3K/Akt/mTOR signaling has been proposed as a possible more effective therapeutic approach for CRPC. However, truncated AR-splice variants (AR-Vs) that are constitutively active and dominant over FL-AR are associated with tumor progression and resistance mechanisms in CRPC. It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 42 publications
(67 reference statements)
4
54
0
Order By: Relevance
“…The present study indicated that thapsigargin significantly decreased cell proliferation, and increased the apoptosis rate and caspase-9/3 activities in PC3 cells. The mTOR signal transduction pathway primarily participates in the synthesis of proteins (20). A previous study concerning the suspected associations between single nucleotide polymorphisms in the signal transduction pathway gene and prostate cancer conducted worldwide (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study indicated that thapsigargin significantly decreased cell proliferation, and increased the apoptosis rate and caspase-9/3 activities in PC3 cells. The mTOR signal transduction pathway primarily participates in the synthesis of proteins (20). A previous study concerning the suspected associations between single nucleotide polymorphisms in the signal transduction pathway gene and prostate cancer conducted worldwide (21).…”
Section: Discussionmentioning
confidence: 99%
“…mTOR is widely expressed in cells and regulates multiple cellular functions in different cells, including survival and proliferation (21). On the one hand, the mammalian target of rapamycin complex 1 regulates translation, including 5'terminal oligopyrimidine tract mRNAs (20). Conversely, mTORC1 serves as the central pivot of the cascade signal channel that regulates RNA translation.…”
Section: Discussionmentioning
confidence: 99%
“…Concurrent inhibition of AR and non-genomic AR components may prove useful for prostate cancer patients with progression after primary therapy. Many of these strategies are currently under investigation and show promising results in preclinical models of CRPC (8285). …”
Section: Implications For Prostate Cancer Therapiesmentioning
confidence: 99%
“…Here, we describe several AR-V-targeting agents that have entered clinical trials for cancer treatment. EPI-001/002 is a small-molecule, non-steroidal AR antagonist that covalently binds to AR N-terminal domain to inhibit the transcriptional activities of AR-FL and AR-Vs (Andersen, et al 2010; Kato, et al 2016; Myung et al 2013; Sadar 2011). It has also been found to act as a selective PPARγ modulator to inhibit AR expression (Brand, et al 2015).…”
Section: Therapeutic Targeting Of Ar-vsmentioning
confidence: 99%